What happens when seniors participate in new eHealth schemes?. (2nd October 2016) - Frennert, Susanne; Östlund, Britt
Abstract: This article adds empirical depth to our understanding of seniors' involvement in the making of eHealth systems. Multi-sited interviews and observations were conducted at seniors' homes before an eHealth system was installed, during the home trials and post-removal of the system. Our findings indicate that although the senior participants chose to participate in the home trials, the choice itself was configured by the stigmatization of seniors as technophobes, fear of "falling behind" and the association of technology with youth, the future and being up-to-date. Being a participant in home trials of an eHealth system became an identity of its own, representing a forward thinking and contemporary person who embraced changes and new technology. Implications for Rehabilitation: This article highlights the importance of understanding the participants' drive to participate in field trials and the impact this motivation has on how, during field trials, they perceive using an eHealth system and its perceived usefulness. When studying eHealth systems "in the making at senior" participants' homes, the seniors become part of the research team. The senior participants' learning and knowledge transfer evolves from the dialogue with the research team. For equal participation and power there is a need for ethical, mutual and equal power-relations in the research team (between researchers from different paradigms such as engineers and sociologists) as well as between the researchers' and the participants'.